A human-specific regulatory mechanism revealed in a pre-implantation model - Raquel Fueyo; Sicong Wang; Olivia J. Crocker; Tomek Swigut; Hiromitsu Nakauchi; Joanna Wysocka (Nature, 2025)
Abstract Stem cell-based human embryo models offer a unique opportunity for functional studies of the human-specific features of development. Here we genetically and epigenetically manipulate human blastoids, a 3D embryo model of the blastocyst 1 , to investigate the functional effect of HERVK LTR5Hs, a hominoid-specific endogenous retrovirus, on pre-implantation development. We uncover a pervasive cis -regulatory contribution of LTR5Hs elements to the hominoid-specific diversification of the epiblast transcriptome in blastoids. Many of the LTR5Hs genomic insertions in the human genome are unique to our own species. We show that at least one such human-specific LTR5Hs element is essential for the blastoid-forming potential via enhancing expression of the primate-specific ZNF729 gene, encoding a KRAB zinc-finger protein. ZNF729 binds to GC-rich sequences, abundant at gene promoters associated with basic cellular functions, such as cell proliferation and metabolism. Despite mediating recruitment of TRIM28, at many of these promoters ZNF729 acts as a transcriptional activator. Together, our results illustrate how recently emerged transposable elements and genes can confer developmentally essential functions in humans.